Railway Planning Double-Double Track (Case Study of Bekasi Station km 26 + 652 - Jatinegara Station km 12 + 050 - Ido Prasetio; Andri irfan rifai (NAROTAMA UNIVERSITY, Indonesia)
Increasing the number of population and the development of activities will cause a growing need for space every day, this will result in physical changes and urban land use and can cause increased intensity of population movement from Megapolitan cities such as Bekasi, Bogor and Tangerang to the Metropolitan city (DKI Jakarta). Some people have now started to move from private vehicles to use public (mass) transportation such as buses, transjakarta, and electric rail trains or commonly known as KRL Commuter Line that serve Jabodetabek routes. The impact of crossing also causes buildup at each station. Train track with a single track (single track) is considered ineffective and inefficient and vulnerable to train accidents due to human error. It is necessary to develop or develop a double track to become a double-double track Bekasi Station km 26 + 652 - Jatinegara Station km 12 + 050. The research location is on the railway line from Bekasi Station to Jatinegara Station. The length of the train track is around 16 km and has 7 stations that are traversed, 5 of which are active (stop) and 2 passive stations.